SPEAKING CLASS BASED COABORATIVE VIRTUAL LEARNING AS MULTILITERACIES CONCEPT - Arjulayana Arjulayana; Zainal Rafli; Ratna Dewanti (Universitas Muhammadiyah Semarang, 2021)
Learning speaking for university students should be creative and innovative. In line with corona virus diseases- 19 most of educational institution need to implement online learning for all the subject, also for speaking class. Speaking skill had taught in collaborative and virtual model in University of Muhammadiyah Tangerang, because collaborative virtual engage student’s critical skill and speaking practice are facilitated well. This model is supported by the potential concept for teaching and learning speaking collaboratively in virtual, it called multiliteracies concept. Multiliteracies is a concept of scientific model in learning meaning , such as; linguistc meaning, gesture meaning, visual, and audio visual meaning. This research uses Class room action research with 35 sample of 2nd semester students from University of Muhammadiyah Tangerang. The result of this research shows that collaborative virtual learning is effective for teaching and learning speaking, because students are encouraged to speak and think directly while doing online discussion, as the implementation of multiliteracies concept for speaking this research also shows that students collaborative virtual learning become enjoyable and productive, because students required to design their own learning model.